Influence of Competence and Independent Auditors on The Quality of Audit - Rita Yulianida; Erpi Rahman; Aa Kartiwa (LPPM Universitas Sebelas April, 2022)
This study aims to determine: 1) the effect of auditor competence on audit quality; 2) The Effect of Auditor Independence on Audit Quality; 3) Correlation of Auditor Competence to Auditor Independence 4) Effect of Competence and Independence of Auditors together on Audit Quality. This research includes causal associative research, namely research with the characteristics of the problem in the form of a causal relationship between two or more variables. The population in this study is the Inspectorate of Sumedang Regency. Samples were taken as many as 23 auditors at the Sumedang Regency Inspectorate. Techniques Data collection is done by using the questionnaire method. The questionnaires were tested for validity and reliability before collecting research data. Prior to the analysis, the analysis prerequisite tests were carried out including linearity test, normality test, multicollinearity test, and heteroscedasticity test. Analysis of the data used to test the hypothesis is to use simple regression analysis techniques and multiple regression analysis techniques. The results showed that: 1) There was a positive and significant effect of Internal Auditor Competence on Audit Quality with t count 7.856 > t table 2.093 and correlation coefficient of 0.874; 2) There is a positive and significant effect of Auditor Independence on Audit Quality with t count 4.221 > t table 2.093 and correlation coefficient of 0.696; 3) There is a correlation between Auditor Competence and Auditor Independence with a correlation coefficient of 0.629; 4) There is a positive and significant effect of Auditor Competence and Independence together on Audit Quality with F count 35.928 > F table 3.52 and the correlation coefficient is 0.894;